Về bàn phím máy tính cho chữ Việt - Việt, Ngô Trung; Do, James; Nhàn, Ngô Thanh; Thành, Hoàng Công (Journal of Computer Science and Cybernetics, 2016)
Vietnamese keyboard i9s an indispensable tool to use Vietnamese on computers. This paper is intended to  present some principals should be considered when designing keyboard for Vietnamese and some problems  of its installation. Vietnamese keyboard should be  conformed main points of  views development of information technology in Vietnam and satisfied four requirements: completeness, consistency, compatibility and  simplicity. Based on  principals of international keyboards, according to standards ISO 9995 and ECMA 115, and some Vietnamese particulars, methods of encoding and  rendering Vietnamese characters from international keyboards are considered and commented. Two solutions for designing Vietnamese keyboard satisfying the four above requirements are proposed.